Development of superphosphate based shells for the production of capsulated environmentally safe fertilizers - Gurets, Larisa; Vaka, Viktoriia; Vaka, Sergiy (Lviv Politechnic Publishing House, 2018)
The perspectivity of attracting ammoniated superphosphate based on phosphorites with content of P2O5 is not less than 19 % as the main phosphate shell component for the encapsulation of urea have been substantiated. The peculiarities of the kinetics of phosphorus decomposition with the formation of ammoniated superphosphate have been established. Examples of its use as a phosphate shell are given. The ecological feasibility of using it as a phosphate shell is shown.
Keywords: phosphate concentrate; superphosphate; encapsulation; phosphate shell; mineral fertilizer